Variation in blubber thickness and histology metrics across the body topography of a false killer whale (Pseudorca crassidens) - Phipps, Jana E.; Silva-Krott, Ilse; Marchetti, Jamie; West, Kristi L. (Frontiers in Physiology, 2023)
Blubber is a multifunctional tissue essential to the survival of cetaceans. Histological assessment of blubber may be useful in determining odontocete nutritional state but a greater understanding of specific variation across the body is needed. We report on morphological variation of the blubber according to girth axes and sampling planes in a sub-adult male, bycaught false killer whale (Pseudorca crassidens) using metrics of blubber thickness (BT), adipocyte area (AA), and adipocyte index (AI). 48 full depth blubber samples were taken along 6 girth axes at 5 equidistant sampling points on both sides of the body. At these sampling locations BT was recorded, and AA and AI were determined for three distinct blubber layers. Linear mixed effect models were used to assess variation of the blubber across layers and body topography. BT was somewhat non-uniform across the body but was generally thicker in the dorsal region and thinner laterally. AA was greater cranially and AI was greater caudally. The middle and inner layer blubber showed significant differences dorsoventrally with larger AA and smaller AI in the ventral region of the body. Variation of the blubber metrics across the body are indicative of variable functions of the blubber within an individual. Due to the variability observed, we expect that AI of the dynamic inner layer blubber is most informative of overall body condition and that biopsy samples of the outer and middle blubber may still be useful in determining the nutritional status of live false killer whales.